1997
DOI: 10.1038/bjc.1997.562
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between vascularity, age and survival in non-small-cell lung cancer

Abstract: Summary Lung tumours in the elderly show reduced growth potential; impaired angiogenesis may contribute to this phenomenon. Recent studies have suggested that the angiogenic potential of a tumour may be inferred by the vascularity measured in histological sections. The purpose of this study has been to determine whether vascularity is related to age, survival or other clinical parameters in resected non-smallcell lung cancer (NSCLC). A group of 88 consecutive patients with a follow-up period of at least 5 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 29 publications
3
41
0
2
Order By: Relevance
“…Information related to the tumours analysed is given in Table 1. All tumour blocks were selected on the basis of containing ample and representative tumour areas in haematoxylin and eosin (H&E) sections as described (Chandrachud et al, 1997).…”
Section: Materials and Methods Specimensmentioning
confidence: 99%
“…Information related to the tumours analysed is given in Table 1. All tumour blocks were selected on the basis of containing ample and representative tumour areas in haematoxylin and eosin (H&E) sections as described (Chandrachud et al, 1997).…”
Section: Materials and Methods Specimensmentioning
confidence: 99%
“…In the 14 remaining eligible studies (Macchiarini et al, 1994;Yamazaki et al, 1994;Fontanini et al, 1995;Mattern et al, 1995;Chandrachud et al, 1997;Giatromanolaki et al, 1997;Takanami et al, 1997;Duarte et al, 1998;Imoto et al, 1998;Aikawa et al, 1999;D'Amico et al, 1999;Ohta et al, 1999;Sheng et al, 2000;Yano et al, 2000), published between 1994 and 2000, the total number of patients was 1866 ranging from 28 to 408. The main characteristics of these 14 studies are shown in Table 1.…”
Section: Studies Selection and Characteristicsmentioning
confidence: 99%
“…Microvessel density seems to be an important prognostic indicator in lung cancer (Fontanini et al, 1995;Giatromanolaki et al, 1997) although some studies have not found microvessel count to be predictive for survival (Chandrachud et al, 1997;Pastorino et al, 1997). Currently, different antibodies to three endothelial cell antigens can be used to visualise the tumour blood vessels by immunohistochemistry: factor VIII antigen or von Willebrand's factor is involved in platelet adhesion and aggregation; CD31 or PECAM 1 (platelet/endothelial cell adhesion molecule) is associated with platelet adhesion in inflammation, wound healing, trans-endothelial cell migration and cell migration; CD34 is involved in leukocyte adhesion and endothelial cell migration during angiogenesis.…”
mentioning
confidence: 99%
“…It is likely that the difficulties with this method have lead to a substantial number of studies in which no correlation (Brechot et al, 1996;Chandrachud et al, 1997;Hillen et al, 1997) or even an inverse correlation (Sarbia et al, 1996;Delahunt et al, 1997) was found between angiogenesis and the aggressiveness of the tumour. This urged researchers to quantify MVD by using image-analysis software (Kirchner et al, 1996;Wild et al, 2000;).…”
mentioning
confidence: 99%